Insulin Treatment May Increase Adverse Outcomes in Patients With COVID-19 and Diabetes: A Systematic Review and Meta-Analysis - Yang, Yan; Cai, Zixin; Zhang, Jingjing (Frontiers in Endocrinology, 2021)
Aims: Recently, insulin treatment has been found to be associated with increased mortality and other adverse outcomes in patients with coronavirus disease 2019 (COVID-19) and diabetes, while the results still remain unclear and controversial, so we conducted this meta-analysis. Methods: Four databases, namely, PubMed, Web of Science, EMBASE and the Cochrane Library, were used to identify all studies on insulin treatment and adverse effects of COVID-19, including mortality, incidence of severe/critical complications, in-hospital admission and hospitalization time. To assess publication bias, funnel plots, Begg’s tests and Egger’s tests were used together. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to access the effect of insulin therapy on mortality, severe/critical complications and in-hospital admission. And the association between insulin treatment and hospitalization time was calculated by standardised mean difference (SMD) with 95% CIs. Results: Eighteen articles were included, with a total of 12277 patients with COVID-19 and diabetes. Insulin treatment was significantly associated with an increased risk of mortality (OR=2.10; 95% CI, 1.51-2.93) and the incidence of severe/critical COVID-19 complications (OR=2.56; 95% CI, 1.18-5.55). Moreover, insulin therapy may increase the in-hospital admission in patients with COVID-19 and diabetes (OR=1.31; 95% CI, 1.06-1.61). However, there was no significant difference in hospitalization time according to insulin treatment (SMD=0.21 95% CI, -0.02-0.45). Conclusions: Insulin treatment may increase mortality and severe/critical complications in patients with COVID-19 and diabetes, while more large-scale studies are needed to be carried out to confirm and explore the exact mechanism.